Theism and Pantheism in Epictetus’ theology: is the personalist language a pedagogical strategy? - Braicovich, Rodrigo Sebastián (Estudios de Filosofía, 2011)
The goal of the present piece is to analyze the interpretation of Epictetus’ Theology recently put forward by Keimpe Algra, which suggests that we interpret the Personalist Language of certain passages of the Dissertations as a Pedagogical Tool beneath which hides an orthodox core. I will point to some important difficulties in Algra’s interpretation which force us to conclude that the traditional interpretation (that interprets the Personalist Language of the said passages in a literal sense, i.e., as the expression of a Theistic and Personalistic Conception of Divinity) still stands.